WITHDRAWN Electrical Properties of Cobalt Substituted NZCF and ZNCF Nanoparticles Prepared by the Soft Synthesis Method (Journal of Nepal Physical Society, 2022)
This article was withdrawn on 7th April 2025.The withdrawal was carried out at the request of the journal’s editor and the corresponding author.